Peran Hubungan Masyarakat (Humas) Dalam Penyebarluasan Informasi Pembangunan Daerah di Kabupaten Bengkalis Riau - Suryani Barimbing; Yunisa Octavia (JIPAGS (Journal of Indonesian Public Administration and Governance Studies), 2022)
The purpose of this analysis is to be able to find out and also analyze how the strategies that can be used by the public relations of the Riau City government in disseminating regional development information. As for the participation of local governments, namely to be able to build "good governance" to be able to develop a dimension of openness, which is easy to access and transparent. In this case, there is also a need for a lot of criticism and opinions from other parties or from public opinion. and an institution that exists in one of the government offices that work to be able to realize a form of transparency, ease of accessing information, while transparency is a field related to government public relations. as for Public Relations (Humas) is very important in order to be able to improve a local government performance in disseminating information to the public or the public. which is where Public Relations (PR) it self will confront, namely between the interests of the local community and also the interests of the government from one party to another in order to improve a development performance in the community and also government activities. so it can be said that the role of Public Relations (PR) is to be able to build a synchronous relationship with the community and also to be able to build a position from one agency in view of the community, in order to be able to receive an understanding and also get a support from the community. Public relations here are also the spearhead of the implementation of local government information. because basically the Regional Apparatus Work Unit (SKPD) and also to be able to establish a relationship with Public Relations. which Public Relations (PR) has an important role in the delivery of information services organized by a local government agency together with the community.Keywords: public relations, local government.